VD_FINDINFO HC / 2023 / 85 vom 13. März 2023 - VD Tribunal cantonal (2023)
PROTECTION DE L'UNION CONJUGALE, REJET DE LA DEMANDE, OBLIGATION D'ENTRETIEN | 163 CC, 176 al. 1 ch. 1 CC, 276 CC, 285 CC, 311 al. 1 CPC (CH)